Peningkatan Kemampuan Menulis Artikel Pustakawan Di Pekanbaru - Rosman H Rosman H; Nining Sudiar; Hadira Latiar (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2020)
Scientific articles are scientific papers from research results communicated in scientific publications, such as journals, magazines, or other publications. Librarians as functional personnel are required to make a positive contribution to the nation's change, one of which is to produce scientific papers published in scientific publications. The community service activities aim to provide understanding, improve and provide the ability to compile research results and the ability to write scientific articles to librarians in Pekanbaru. The method used in this activity is in the form of workshops delivered with lecture techniques, question and answer, and practice. To find out the extent of participants' acceptance and understanding, as well as the ability of participants, at the beginning and end of the training an evaluation or evaluation is carried out by filling in the pretest and post-test sheets. Based on the results of the tests that have been conducted, it is known that the participants experienced an increase after training in writing scientific articles. On the understanding of the concept of scientific articles increased by 30.75%, while the ability of strategies and scientific article writing techniques increased by 29.64%. in the training participants were very enthusiastic and active in participating in training activities writing scientific articles from beginning to end.